Effect of curcumin dietary supplementation on growth performance, physiology, carcass characteristics and meat quality in lambs - Marcon H.* (2021)
© 2021 Sciendo. All rights reserved.This study evaluated the effects of curcumin dietary supplementation on growth, physiology, carcass characteristics and meat quality in lambs. Thirty-two male Lacaune lambs (15.6±0.63 kg, 60±2.8 days of age) were randomly allocated in 16 pens (four treatments of four replicates with two lambs each) for 30 days. The animals were assigned to the following treatments: T0, T100, T200 and T300, representing 0, 100, 200 and 300 mg of curcumin/kg of concentrate, respectively. Curcumin dietary supplementation increased (P=0.02) weight gain; on regression analysis, 315.1 mg curcumin/kg of concentrate was the dosage that provided the greatest weight gain. T200 and T300 lambs had lower (P=0.04) erythrocyte numbers; T100 and T300 lambs had lower (P=0.01) leukocyte numbers and T300 lambs had lower (P=0.04) lymphocyte numbers, compared to T0 lambs. Globulin levels were significantly greater in the T200 group (P=0.04) only on day 15 but not day 30; levels of total protein were significantly higher (P=0.01) only in T200 and T300 groups on day 15 and only in T200 group on d 30. Gamma-glutamyltransferase concentrations tended to be lower (P=0.08) in T100, T200 and T300 groups on d 15, and only in the T100 group on d 30. Curcumin dietary supplementation increased (P=0.01) the serum activity of antioxidant enzymes and reduced (P=0.01) levels of reactive oxygen species. In meat samples, T200 and T300 had greater total antioxidant capacity (P=0.03) and lower (P = 0.01) lipoperoxidation rates. In carcasses, T300 lambs had greater (P≤0.02) cooling weight losses and yields than did T0 lambs. Curcumin dietary supplementation also reduced (P≤0.03) redness and yellowness. T200 and T300 lambs had fewer (P=0.01) cooking losses and T200 lambs had greater (P=0.03) water holding capacity than did T0 lambs. These findings suggest that curcumin dietary supplementation improves growth and antioxidant responses, as well as influencing meat quality in lambs.